Validity and reliability analysis of a higher education decision-making instrument in Central Kalimantan - Guntoro, Dibyo Waskito; Munandar, Haris; Ziaurrahman, Muhammad (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
This study aims to analyze the validity and reliability of an instrument developed to measure the factors influencing students’ decision-making in pursuing higher education in Central Kalimantan. Employing a quantitative descriptive design with a survey method, the instrument was constructed based on eight components: Individual Factors, Family Background, Training Activities, Social Factors, Cultural Influences, Achievement, Attitudes toward Institutional Factors, and Price Sensitivity. The questionnaire consisted of 48 Likert-scale items administered to 98 senior high school students from various districts in Central Kalimantan. Item validity was examined using the Pearson Product-Moment correlation, while reliability was assessed using Cronbach’s Alpha with the aid of SPSS. The analysis identified 30 items as valid and reliable indicators, meeting the statistical criteria for inclusion. The final instrument demonstrated strong internal consistency, with a Cronbach’s Alpha coefficient of 0.880. These findings confirm that the instrument is psychometrically sound and suitable for use in further research related to higher education decision-making. The validated scale provides a comprehensive framework for understanding the diverse individual, social, cultural, and institutional factors influencing students’ choices, particularly within the Central Kalimantan context.